Otimização do fluxo da informação no diagnóstico preventivo do câncer de colo de útero - Franco, Ramon Adrian Salinas (2015)
Many studies have been conducted recently in order to understand cervical cancer and the best way to prevent it. The most successful mechanism for the prevention of cervical cancer is the Pap test. This popular exam is performed continuously throughout Brazil, and although the Pap test is quick and painless, the results can take as long as up to six months. This ultimately causes many women to give up on the exam. In recent years, science and technology has allowed for the creation of new ways to conduct noninvasive diagnosis. The general objective of this research is to propose a method to reduce the response time in delivering the result of a Pap test through the analysis of information flows and the incorporation of information and communication technologies. The methodology used in this research was exploratory. The literature search was performed through the use of scientific databases, covering books, articles, publications, dissertations, theses, among other sources of information relevant. Data collection was carried out by reading multiple sources and examples of existing models. As a starting point, information from the literature was used to understand the operation of the collection Pap tests and following information about the exam in São Carlos / SP, including the advice of experts. As a comparative object for research, a technological tool that was used in Colombia, optimizes the information flows of the Pap test. The results were obtained in relation to the identification of information flows proposed model of more efficient than traditional models surveyed by data collection and evaluation test. The information flows were analyzed composing the Information System for the realization of the Pap smear, including Galenic Tele Salud software modified to Brazilian conditions and was obtained using the model proposed a time of 76.85 minutes with 20 simulations, demonstrating that the proposed model is more efficient than the traditional models studied. It is believed that this research offers a contribution to enable new studies and new methods to facilitate and improve the activities required for the realization of the Pap smear.